PERAN UNITED NATION CHILDREN FUND (UNICEF) DALAM MEMBERIKAN BANTUAN TERHADAP ANAK-ANAK KORBAN KRISIS KEMANUSIAAN DI ELSALVADOR TAHUN 2019-2022 - Nazala, Zawiadah Alyara; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This study explains the role of UNICEF in providing assistance to children who are victims of the humanitarian crisis in El Salvador in 2019-2022. UNICEF as an International Organization is present as one of the solutions in determining the resolution of humanitarian problems, especially for children. El Salvador has a history of humanitarian crises caused by various things including gang violence, mass immigration, poverty and natural disasters. This problem has an impact on children so that children are the main victims who are most affected. UNICEF plays a crucial role in supporting education, health, and child protection in El Salvador. The El Salvador government is considered to have failed to provide solutions to the problems of this country. The government has been criticized for human rights violations in implementing their solutions, so the role of a third actor is needed, namely the Independent Actor. This study uses a qualitative method with data collection techniques through literature studies sourced from several books, journals, articles, and websites. This study uses the theory of International Organization and has a research focus from 2019 to 2022. The results of this paper present some of UNICEF's efforts in providing assistance to children in El Salvador through the Humanitarian Act for Children and Country Development Program (CDP). Keywords:UNICEF, Humanitarian Crisis, Kids, El Salvador.